Development of electrostatic‐induced charge detector for multiturn time‐of‐flight mass spectrometer By Ken‐ichi Bajo, Jun Aoki, Morio Ishihara, Shizuho Furuya, Masahiro Nishimura, Miwa Yoshitake and Hisayoshi Yurimoto. (22nd November 2022) - Bajo, Ken‐ichi; Aoki, Jun; Ishihara, Morio; Furuya, Shizuho; Nishimura, Masahiro; Yoshitake, Miwa; Yurimoto, Hisayoshi
Abstract :